1990
DOI: 10.1037/0022-3514.58.4.610
|View full text |Cite
|
Sign up to set email alerts
|

Pardon my gaffe: Effects of sex, status, and consequence severity on accounts.

Abstract: Examined the effects of offender sex, offender status, and consequence severity on accounts following an embarrassing predicament. Subjects were induced to believe they had committed a gaffe with either relatively mild or severe consequences for a confederate/victim of either higher or lower status than they, and their verbal and nonverbal behaviors captured on videotape served as the source of dependent variable measures. Verbal accounts were coded using Schonbach's (1980) account taxonomy. Nonverbal behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
5
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(108 citation statements)
references
References 23 publications
7
92
5
4
Order By: Relevance
“…We found that respondents rated male supervisors in a vignette more transformational in both the apology and no apology conditions. These findings are somewhat surprising given findings from other studies which suggest that females are generally rated higher in transformational leadership (Eagly et al, 2003) and tend to offer more and richer concessionary accounts for perceived interpersonal breaches than males (Gonzales et al, 1990(Gonzales et al, , 1992. We offer three possible explanations for these unexpected findings.…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations
“…We found that respondents rated male supervisors in a vignette more transformational in both the apology and no apology conditions. These findings are somewhat surprising given findings from other studies which suggest that females are generally rated higher in transformational leadership (Eagly et al, 2003) and tend to offer more and richer concessionary accounts for perceived interpersonal breaches than males (Gonzales et al, 1990(Gonzales et al, , 1992. We offer three possible explanations for these unexpected findings.…”
Section: Discussioncontrasting
confidence: 43%
“…There is also some evidence suggesting that perceptions of leaders who apologize may be influenced by leader gender. Laboratory-based studies have found that women tend to offer more frequent and richer apologies than men (Gonzales et al, 1990(Gonzales et al, , 1992. In contrast, men are more likely to avoid apologizing, and instead show a greater preference to use aggravating accounts such as denials (e.g., Hodgins and Liebeskind, 2003).…”
Section: Apologies and Socially Constructing Leadershipmentioning
confidence: 91%
See 2 more Smart Citations
“…Beyond the content of what is communicated, account-giving research finds that account acceptance is affected by the social context (e.g., by whom it is said, how it is said, and to whom it is said; Gonzales, Pederson, Manning, & Wetter, 1990;McLaughlin, Cody, & O'Hair, 1983;Niedermeier, Horowitz, & Kerr, 2001). Indeed, recent counterfactual research supports this notion.…”
Section: Future Researchmentioning
confidence: 74%